2017
DOI: 10.1021/acs.biochem.7b00500
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Induced Facilitated Dissociation of the Competitive Inhibitor from the Active Site of O-Acetyl Serine Sulfhydrylase Reveals a Competitive-Allostery Mechanism

Abstract: By classical competitive antagonism, a substrate and competitive inhibitor must bind mutually exclusively to the active site. The competitive inhibition of O-acetyl serine sulfhydrylase (OASS) by the C-terminus of serine acetyltransferase (SAT) presents a paradox, because the C-terminus of SAT binds to the active site of OASS with an affinity that is 4-6 log-fold (10-10) greater than that of the substrate. Therefore, we employed multiple approaches to understand how the substrate gains access to the OASS activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Further, both interact to form a stable multi-enzyme complex, referred to as Cysteine Regulatory Complex (CRC) [15][16][17]. Our recent studies showed that CRC complex dissociates in the presence of OAS, the substrate of CS, at stoichiometric concentrations [1,18]. Dissociation of CRC at stoichiometric concentration of OAS was not expected as previous studies reported that affinity of SAT (inhibitor) is 4-6 log-fold higher than that of OAS [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Further, both interact to form a stable multi-enzyme complex, referred to as Cysteine Regulatory Complex (CRC) [15][16][17]. Our recent studies showed that CRC complex dissociates in the presence of OAS, the substrate of CS, at stoichiometric concentrations [1,18]. Dissociation of CRC at stoichiometric concentration of OAS was not expected as previous studies reported that affinity of SAT (inhibitor) is 4-6 log-fold higher than that of OAS [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 96%
“…Proteases accomplish substrate-specificity through specific sub-pockets (S1, S2), mostly non-catalytic residues, distributed within the active site [10,13]. Similarly, the active site of cysteine synthesis enzyme (CS) is mapped into three sub-pockets (S1, S2, S3) that coordinate the substrateinduced conformational transition to closed state [1]. In a recent study, we showed that substrate-binding induced active site conformational changes allowed CS to selectively recruit its substrate, O-acetyl serine (OAS), in the presence of high affinity natural inhibitor, the C-terminal of serine acetyl transferase (SAT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work with a variety of biomolecules such as transcription factors (20,22,(24)(25)(26)(27)(28)(29), metalloregulators (21,30), chromatin effectors (31), DNA polymerases (32)(33)(34)(35)(36), antibody-antigen complexes (37), and other biological complexes (23,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) has demonstrated that facilitated dissociation, in which protein dissociation rates depend on ambient protein or other biomolecule concentration, is a widespread phenomenon both in vitro and in vivo. Facilitated dissociation contrasts with classical kinetic models of bimolecular complexes that undergo simple, binary on/ off transitions and have concentration-dependent association rates and concentration-independent dissociation rates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work with a variety of biomolecules, such as transcription factors (20,22,(24)(25)(26)(27)(28)(29), metalloregulators (21,30), chromatin effectors (31), DNA polymerases (32)(33)(34)(35)(36), antibody-antigen complexes (37), and other biological complexes (23,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) has demonstrated that facilitated dissociation, in which protein dissociation rates depend on ambient protein or other biomolecule concentration, is a widespread phenomenon both in vitro and in vivo. Facilitated dissociation contrasts with classical kinetic models of bimolecular complexes that undergo a simple, binary on/off transitions, and have concentration-dependent association rates and concentration-independent dissociation rates.…”
Section: Introductionmentioning
confidence: 99%